PROSPEK PENGEMBANGAN UBI JALAR DALAM MENDUKUNG KETAHANAN PANGAN DI KABUPATEN MANGGARAI BARAT - Maria Alfonsa Ngaku; Marten Umbu Kaleka; Antonia P Bao; Umbu N Limbu (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Sweet potato is also a commodity that can increase farmers. Sweet potato is also a food need that is a source of carbohydrates and a source of vegetable protein so that it is widely cultivated by the wider community, one of which is in West Manggarai Regency. This research uses qualitative research methods. The type of data used is secondary data sourced from print media, online media such as BPS data of West Manggarai Regency and journals. The method used in this assessment is literature study. It is seen that the amount of planting area (Ha) to be planted with sweet potatoes from 12 sub-districts in West Manggarai Regency with a total of 930 Ha. For the harvest area (Ha) of sweet potato is 930 (Ha) with a production level (Tonnes) of sweet potato in April-September 2022 which is 10,230.00 Tonnes. It can also be seen that sweet potato production in West Manggarai Regency is quite high. The high production of sweet potatoes is because farmers have carried out sweet potato cultivation activities correctly. Sweet potatoes are generally planted in rain-fed rice fields after the rice planting period ends and left to grow without intensive care. The sweet potato does not have a brand or has not been processed properly. Sweet potatoes themselves are still processed traditionally, such as steamed and fried. Seeing this, it is necessary for the government to take advantage of opportunities so that sweet potatoes can be recognised by the wider community.